Baers in Congenital Hydrocephalus - J Gordon Millichap (Pediatric Neurology Briefs)
Brainstem auditory evoked responses were studied in 20 children with congenital hydrocephalus before and after shunt surgery at the Departments of Neurosurgery and Neurology, National Institute of Mental Health and Neurosciences, Bangalore, India.